Synthesis of the new analogs of morpholine and their antiplasmodial evaluation against the human malaria parasite Plasmodium falciparum. (3rd December 2021) - Upadhyay, Charu; Sharma, Neha; Kumar, Sumit; Sharma, Prem Prakash; Fontinha, Diana; Chhikara, Bhupender S.; Mukherjee, Budhaditya; Kumar, Dhruv; Prudencio, Miguel; Singh, Agam P.; Poonam,
Abstract : A series of morpholine analogs functionalized with hydroxyethylamine (HEA) pharmacophore was synthesized and assayed for the initial screening against Plasmodium falciparum 3D7 in culture, which suggested that analog 6k is a hit molecule with an inhibitory concentration of 5.059 ± 0.2036 μM. Abstract : A series of morpholine analogs functionalized with hydroxyethylamine (HEA) pharmacophore was synthesized and assayed for the initial screening against Plasmodium falciparum 3D7 in culture, which suggested that analog 6k is a hit molecule with an inhibitory concentration of 5.059 ± 0.2036 μM. Listed analogs were also assessed for toxicity against liver cells, HepG2, and none of them showed cytotoxicity up to 2 mM. Further, we tested all the compounds against a validated target, plasmepsin X, and the results were supported with molecular docking and molecular dynamic simulation. Overall, these novel compounds demonstrated moderate antiplasmodial activity without any toxic effects, and therefore medicinal chemistry optimization is essential to obtain analogs with improved biological activity.